Transition Between Sensitive Delusion of Reference and Mood Disorder: A Case Report - Esposito, Cecilia Maria; Fiorentini, Alessio; Callari, Antonio; Galeazzi, Gian Maria; Brambilla, Paolo (Frontiers in Psychiatry, 2021)
The Sensitive Delusion of Reference is a clinical entity described by Ernst Kretschmer and never integrated in mainstream nosographic systems. It represents the possibility of developing psychosis starting from a personality characterized by sensitivity, scrupulousness, fear of the judgment of others. The presentation of the following clinical case highlights how the overlap between this clinical entity and mood disorders lead to a characteristic psychopathology, which has not been sufficiently detailed.. In particular, the delusions, while always starting from the idea of reference and the shame in the face of the judgment of others, takes on characteristics of guilt during the depressive phases and persecutory themes during the activation phases. This clinical observation, which obviously needs to be confirmed on a larger scale, encourages a renewed interest in the concept of Kretschmer's Sensitive Delusion of Reference, and opens to the possibility of intersecting multiple psychopathological levels, for a more complete perspective on the individual case.